Novel approaches for functionalization of polypropylene by maleimides. (3rd January 2022) - Korčušková, Martina; Petruš, Josef; Lepcio, Petr; Kučera, František; Jančář, Josef
Abstract: The hydrophobic character of polypropylene (PP) limits its miscibility with more hydrophilic components and fillers. One approach to answer this challenge is the PP functionalization with hydrophilic groups such as maleimides which improves the compatibility in polymer blends and composites, but also improves the thermal stability, allows self-healing or thermal responsivity of the material. In this study, a maleimide-functionalized PP was prepared by the process of reactive grafting with three methods differing in the feed composition: Method A – one-step process, method B – grafting of PP with maleic anhydride and subsequent reaction with amine and method C – reaction between maleic anhydride and amine to form maleimide and subsequent radical grafting of maleimide onto PP backbone. Functionalization was performed with two low molecular weight aromatic amines (aniline, 4-aminophenol) and two high molecular weight aliphatic amines. Maleimide-functionalized PP was also prepared by direct grafting of N -phenylmaleamic acid in the presence of a desiccant that induced a dehydration, forming the maleimide on the PP backbone. The presence of maleimide units were identified by Fourier transform infrared spectroscopy (FTIR). Effect of functionalization on thermal and rheological properties was analyzed by differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and melt volume rate measurement (MVR). Direct grafting of maleamic acid simplifies the technological process of functionalization and provides material and time savings. Graphical abstract: Image 1 Highlights: PP functionalized with maleimides was prepared by reactive grafting via reaction between MAH and amines by 3 methods. Structure, thermal and rheological properties were evaluated. Highest imidation efficiency has been achieved by polypropylene grafting with previously synthetized maleimide. Technological simplification is achievable by direct grafting of PP with maleamic acid in the presence of desiccant P4 O10 .